Tetraspanin 1 (TSPAN1) promotes growth and transferation of breast cancer cells via mediating PI3K/Akt pathway. Issue 2 (20th December 2021) - Wu, Yange; Chen, Wenxiu; Gong, Yufeng; Liu, Hongxia; Zhang, Bo
ABSTRACT: The incidence and mortality of breast cancer rank first among all types of female tumors. To improve patients' prognosis with advanced breast cancer, new and more effective targets still need to be explored and identified. Tetraspanin 1 (TSPAN1) is highly expressed in several cancers and affects the progression of these tumors. However, there are few studies focused on its role in breast cancer. Previous study showed that TSPAN1 promoted epithelial-mesenchymal transition (EMT) and metastasis, and whether TSPAN1 could promote breast cancer via regulating EMT needs further study. In this study, we found high TSPAN1 expression in breast cancer tumor samples and cell lines which was confirmed by bioinformation analysis. The ablation of TSPAN1 suppressed the growth, and motility of breast cancer cells. We further found that TSPAN1 affected the EMT and mediated the PI3K/Akt pathway in breast cancer cells. In addition, TSPAN1 depletion suppressed tumor growth of breast cancer in mice. In summary, we thought TSPAN1 suppressed growth and motility of breast cancer via mediating EMT and PI3K/AKT pathway, and could serve as a potential target for treatment of breast cancer.